Exploring the application of behaviour change technique taxonomies in childhood obesity prevention interventions: A systematic scoping review - Debapriya Chakraborty; Bronwyn A. Bailey; Anna Lene Seidler; Serene Yoong; Kylie E. Hunter; Rebecca K. Hodder; Angela C. Webster; Brittany J. Johnson (Preventive Medicine Reports, 2022)
Behaviour change technique (BCT) taxonomies provide one approach to unpack the complexity of childhood obesity prevention interventions. This scoping review sought to examine how BCT taxonomies have been applied to understand childhood obesity prevention interventions targeting children aged 12 years or under and/or their caregivers. A systematic search was conducted in Medline, Embase, PsycINFO, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, CINAHL and PROSPERO, to capture all eligible research up to February 2021. No limits were placed on country, language, publication dates, or full text availability. Eligible studies included any study design that applied a BCT taxonomy and evaluated behavioural childhood obesity prevention interventions targeting children aged 12 years or under and/or their parents or caregivers. Sixty-three records, describing 54 discrete studies were included; 32 applied a BCT taxonomy prospectively (i.e., to design interventions) and 23 retrospectively (i.e., to assess interventions), 1 study did both. There was substantial variation in the methods used to apply BCT taxonomies and to report BCT-related methods and results. There was a paucity of detail reported in how BCTs were selected in studies applying BCT taxonomies prospectively. Our review provides important insight into the application of BCT taxonomies in childhood obesity prevention and several ongoing challenges, pointing to the need for best practice reporting guidance.